Residential Segregation: Empirical Evidence of the Influence of Human Capital in the City of Armenia, Colombia (2021)
This study simultaneously analyzes residential segregation and human capital composition for the city of Armenia (Colombia). In addition, questions about the existence of polar groups in terms of labor force qualification are raised. Thus, based on census data for 2018, indices of residential segregation increased were calculated by spatial effects and spatial econometric models. The results show that the endowments of human capital in the labor market have spatial externalities among the sectors in this city.